Stres Dan Pemberian Asi Pada Ibu Post Sectio Caesarea Di Poli Obstetri Ginekologi - Rohanifah; Setyo Dwi Andhini, Citra; Suci Astuti, Apriani (LPPM ITEKES Mahardika, 2025)
Postpartum stress is the pressure or psychological burden experienced by mothers after giving birth. Babies should be exclusively breastfed for at least 6 months and continue until the age of 2 years. The purpose of this study was to determine the relationship between stress and breastfeeding in post-cesarean section mothers. This study used a correlational design with a cross-sectional approach. Respondents were 49 post-cesarean section mothers who visited the Obstetrics and Gynaecology Clinic of RSUD, selected using purposive sampling. The instruments used were the Maternal Postpartum Stress Scale (MPSS) to measure stress levels in postpartum mothers and the Breastfeeding and Milk Expression questionnaire. Serveri (BaByMAkeRS). Data analysis used the Spearman test. The results showed that 55.1% moderate stress, post-cesarean section mothers who breastfed directly were 65.3%. The results of the Spearman rank test p-value 0.000 < α (0.01), r = 0.562, then Ha is accepted and H0 is rejected, which means there is a relationship between stress and breastfeeding in post-cesarean section mothers in the obstetrics and gynaecology clinic of RSUD. The higher the stress level, the worse the breastfeeding and vice versa, the less stress, the better the breastfeeding.